#TITLE_ALTERNATIVE# - (NIM 22289006), Sudarmoyo
ABSTRACT: A Streamline model using Lins bounding method have been used to determine both the shape and drainage area of production wells in bounded reservoirs, especially for multi-well variable-rate case. The validity of this streamline simulator that be used for simulating the reservoir models is proved by comparing with the calculated dimensionless-pressure-drop function which has been published for the same reservoir models. The solutions are based on two different methods, i.e superposition of real production time (SRPT) and superposition of pseudo production time CSPPT) methods. The drainage area of production wells obtained by the SPPT method have a difference of less than 5% compared to the results of the SRPT method and it is more efficient in computing time which about 10%-20%. The wells drainage shapes obtained by the SPPT method is relatively same compared to the result of the SRPT method.